Ecological civilization, authoritarian environmentalism, and the eco-politics of extractive governance in China. Issue 3 (July 2020) - Lo, Kevin
Highlights: The national push for an ecological civilization is under way in China. Environmental governance has become more authoritarian. Central environmental polices trump local protectionist instinct. Environmental objectives are achieved at a high socioeconomic cost. Environmental policies impose unfair burdens on disadvantaged communities. Abstract: With the national push for an ecological civilization under way, Chinese environmental governance is becoming more authoritarian as the central government exerts a stronger control over the enforcement of environmental policies. In this paper, I examine how the ecological civilization project has become a key driver of change in extractive regions, constituting new eco-politics of extractive governance that can be characterized by heightened authoritarian environmentalism, with the Central Environmental Inspection Team as a particularly important mechanism through which the centralization of environmental governance is achieved. I argue that the ambitious environmental goals of an ecological civilization are achieved by sacrificing the interests of extractive communities. As these vulnerable communities are highly dependent on their extractive industries and often face significant diversification difficulties, the eco-civilization project has devastating local socioeconomic impacts and are likely to accelerate structural decline and population shrinkage if not promptly addressed through external support. I argue that this constitutes a form of environmental injustice, where environmental policies impose unfair burdens on disadvantaged individuals and communities. In particular, extractive communities bear the greatest burden of both environmental exploitation and environmental protection. Achieving socially just environmental sustainability should be an important aspect of ecological civilization.